Prevention of heart embolic complications in atrial fibrillation: Possibilities of using rivaroxaban - I S Iavelov (Терапевтический архив, 2013)
The review analyzes the role of atrial fibrillation concurrent with stable manifestations of coronary heart disease when novel oral anticoagulants are used. It gives the results of comparison of the efficacy and safety of warfarin and rivaroxaban in such patients in the large controlled ROCKET-AF trial.